O Banrisul entre projetos: os governos de Ildo Meneghetti e de Leonel Brizola (1955-1963) - Silva, Yuri Batista da (2024)
The present study aimed to comprehend various aspects and transformations that occurred in BANRISUL during two distinct state governments: the first, led by Ildo Meneghetti of the Partido Social Democrático (PSD), between 1955 and 1959; the second, by Leonel Brizola of the Partido Trabalhista Brasileiro (PTB), between 1959 and 1963. The analysis encompassed various elements related to banking practices, seeking to articulate them. In the introduction, relevant points about the bank's history and the economic context of Rio Grande do Sul were highlighted. In the second chapter, the electoral campaigns of the winning coalitions in the 1954 and 1958 elections were examined, with an emphasis on proposals and speeches related to Banrisul. The third chapter aimed to deepen the understanding of the profile of shareholders, directors, and advisors of the bank during the specified period. The fourth chapter addressed some of the main activities linked to Banrisul and its development during the defined temporal scope. Finally, in the concluding remarks, the main conclusions reached by this study were presented. Through a comparative perspective, these stages allowed the identification of changes and continuities related to Banrisul and how they were related to the established governments and the broader context.